Repercussão da perda de peso na velocidade de crescimento de crianças e adolescentes: um estudo de caso - Carolina Paniago Lopes; Mariana Porto Zambon; Maria Ângela Reis de Góes Monteiro Antonio (Sociedade Brasileira de Pediatria, 2023)
Report of the longitudinal evolution of the anthropometric indices of an obese child from preschool to the end of the puberty. It is about a 4 year-old boy with history of weight gain since the first year due to carbohydrate-rich and industrialized food intake, associated with physical inactivity and familiar history of obesity. At the first appointment he had body mass index (BMI) in Z-score + 7,36 and stature above the parental target. After orientations about lifestyle changes, he reached, at 7 years old, the lowest BMI and the growth rate became reduced. At this point, other causes of growth retardation have been ruled out, therefore the hypothesis was of growth stop secondary to weight loss and recanalization of the growth curve in response to the treatment of the exogenous obesity. In the evolution, the patient regained weight maintaining the drop on the stature, staying within the parental target. When puberty started, hepresented progressive fall in BMI score and increased growth velocity. At 17, he reached BMI and stature within normality and parent target. Throughout the follow-up, the importance of healthy eating and realization of physical activity was reinforced. No medications were used, and there were no alterations at physical and complementary exams.The weight loss in obese children with tall stature for the parental target, can lead to slow growth rate when secondary to change to healthy habits and increase in physical activity, however without affecting the final height.